Corrosion Behavior of Pure Magnesium with Low Iron Content in 3.5 wt% NaCl Solution. Issue 7 (1st January 2015) - Yang, Lei; Zhou, Xiaorong; Curioni, Michele; Pawar, Surajkumar; Liu, Hong; Fan, Zhongyun; Scamans, Geoff; Thompson, George
Abstract : The microstructure and corrosion behavior of pure magnesium, with 25 ppm Fe but a high corrosion rate, have been studied in this work. It was found that Fe-rich particles, containing also Si, distribute non-uniformly in the Mg matrix and they are spaced at a distance of 100–1000 μm. Before the initiation of localized corrosion, Fe-rich particles play a key role in determining the overall corrosion behavior by supporting hydrogen evolution. During corrosion propagation, Fe-rich particles could be oxidized once they were detached from the Mg matrix and, consequently, lose their cathodic activation. Once the corrosion has taken place over majority of the surface, the effects of crystallographic orientation of the underlying metal dominate the last stage of corrosion, which propagates parallel to the (0001) planes.